Proposal for an Educational Program on Non-Communicable Diseases: Diabetes Mellitus. - Corella Aldama, Sunilda; Teresa Diaz Soto, María; Olivera Ruano, Lourdes; Waterberg Colarte, Joy; Capote Marrero, Belina (Journal of Neonatal Surgery, 2025)
Non-communicable diseases affect all socioeconomic groups, ages, sexes and are the leading cause of death worldwide, contributing to the increase in population aging. Education is at the center of the new trends and chronic diseases are preventable, being necessary health promotion and education programs. The present work was elaborated with the main objective of proposing an educational program on non-communicable diseases directed to patients and health personnel in patients with Diabetes Mellitus, in the "Health Surveillance Establishment" Center, in Kasabaholoweg in Suriname. A preliminary, qualitative-quantitative, descriptive and cross-sectional study is presented. For data collection, an interview was used, a documentary review and for information processing, the Excel 2013 program was used to identify the deficiency of knowledge that these patients had and to be able to carry out the proposed educational intervention. The interviews conducted reflected the patients' lack of knowledge of their pathology and how to prevent its complications. In the educational intervention, topics related to diabetes were addressed; nutrition, physical activities and adequate medical treatment, as well as hygiene and personal cleanliness in patients with this pathology, obtaining as results: in the pre intervention questions were asked to measure the level of knowledge of patients about their disease, in the post educational intervention a considerable increase in the level of knowledge acquired about self-care actions was observed in patients and health personnel, dynamics that were related to the pathology were addressed, to put into practice what was learned. The activity concluded with a reflection and a video on self-care in diabetes.